التفسير والعلاج المعرفي لاضطراب الشخصية الحدية - بن عزوزي, ابراهيم; برخيسة, مريم (جامعة الوادي - University of Eloued, 2020)
يعتبر اضطراب الشخصية الحدية من بين الاضطرابات الأكثر صعوبة على مستوى الفهم والتفسير وكذا العلاج، وهذا ما جعل المقاربات المعرفية توليها أهمية بالغة من خلال وضع نماذج ومقاربات تفسيرية مختلفة، واقتراح برنامج علاجي معرفية سلوكي نموذجي للتعامل مع هذه الحالات. Borderline personality disorder is one of the most difficult disorders in terms of understanding, interpretation and approach, and treatment. This has made cognitive approaches attach importance to them by developing different interpretive models and approaches, and proposing a typical behavioral cognitive therapeutic program to deal with these conditions.
Interpretation and approach and cognitive therapy for borderline personality disorder
مقال
Keywords: اضطراب الشخصية الحدية ; المقاربات المعرفية السلوكية ; العلاج المعرفي السلوكي; borderline personality disorder;cognitive-behavioral approaches;cognitive-behavioral therapy.